Role of Phosphorus and Carbohydrates in Regeneration of Forage Oat (Avena Sativa L.) Genotypes (Global Journal of Science Frontier Research, 2019)
Oat (Avena sativa L.), has received significant attention for its high content of phytochemicals, dietary fibers, and nutritional value. Taking one cut for fodder and grain production from regrowth improves the economic of multi cut fodder oats cultivation. However, information regarding the regrowth and biochemical constituents in these species is not available. The aim of the present study was to evaluate the biochemical and nutritional attributes for regrowth of oat genotypes. Two genotypes viz., HFO865 and HFO873 showed a respectively great increase in fresh weight from first cut (37.79 and 40.55 %) to second cut (87.56 and 72.66 %). Roots and stubbles had a high content of phosphorus and low content of total soluble sugars, thus indicating that phosphorus plays a definite role in regeneration. HJ-8 was observed to have the highest phosphorus content. Fructan decreased with cut systems, but still content was highest in HJ-8. In grains, maximum starch (59.44 %) was highest in HFO870. Crude protein was maximum in Dunav-1 (18.76 %), β-carotene was found highest in HJ-8 and Kent with the value of 110.31 μg/g. The study indicates that Phosphorus, fructan and carbon content playing a crucial role in the regeneration of multi cut genotype (viz. HJ8).
Keywords: fructans; multi cut; nutritional value; phosphorus; regeneration